The Oxford handbook of the historical books of the Hebrew Bible - Kelle, Brad E. 1973-; Strawn, Brent A. 1970- (Oxford Oxford University Press USA - OSO, 2020)
This collection of essays provide resources for the interpretation of the "Historical Books" of the Hebrew Bible that includes the books of Joshua, Judges, Samuel, Kings, Chronicles, Ezra, and Nehemiah. The contributors to this collection are guided by two primary questions: (1) What does this topic have to do with the Old Testament Historical Books? and (2) How does this topic help readers better interpret the Old Testament Historical Books? By first providing a critical survey of prior scholarship, each essay prepares the reader before presenting current and prospective approaches to understanding these texts.
Cover -- The Oxford Handbook of the Historical Books of the Hebrew Bible -- Copyright -- Editorial Preface -- Contents -- List of Abbreviations -- List of Contributors -- Introduction -- Part I: Contexts: Sources, History, Texts -- Chapter 1: Historiography and History Writing in the Ancient World -- 1.1 On Recognizing (and Defining) Historiography -- 1.2 Historiography in the Ancinet World -- 1.3 Sources in the Historical Books -- 1.4 Communicating Significance and Meaning -- Bibliography -- Chapter 2: Assyrian and Babylonian Sources -- 2.1. Israel and Judah in Assyrian Records -- 2.2. Judah and Judeans in Babylonian Sources -- 2.2.1 Neo-Babylonian Chronicles -- 2.2.2 Palace Archives of Nebuchadnezzar II -- 2.2.3 Administrative and Economic Texts -- 2.3. The Significance of the Assyrian and Babylonian Sources -- Note -- Bibliography -- Chapter 3: Achaemenid Political History and Sources -- 3.1 Sources -- 3.1.1 Classical Writers -- 3.1.2 The Old Testament -- 3.1.3 Sources in the Old Persian Script -- 3.1.4 Documents in Other Languages -- 3.1.5 Archaeological Exploration -- 3.2. Imperial Government and Administration -- 3.2.1 Satraps and Subjects -- 3.2.2 Regional Variation -- 3.2.3 Central Control -- 3.3 The King and Royal Ideology -- 3.3.1 Succession and Coronation -- 3.3.2 The Dynamics of Absolute Power -- Notes -- Bibliography -- Chapter 4: Text-Critical Issues with Samuel and Kings -- 4.1. Samuel -- 4.1.1 Manuscript Evidence -- 4.1.1.1 Possible Variant Literary Editions of the Book of Samuel -- 4.1.1.2 Isolated Insertions -- 4.1.1.3 Individual Textual Variants -- 4.1.1.4 Orthographic Differences -- 4.1.2 Assessment of Textual Evidence -- 4.2. Kings -- 4.2.1 Manuscript Evidence -- 4.2.2 The Textual Growth of Kings: Additions and Double Readings -- 4.2.3 The Hexaplaric Additions -- 4.2.4 The Antiochene Text.
Description based on publisher supplied metadata and other sources
Keywords: Bible.-Historical Books-Criticism, interpretation, etc; Electronic books; Aufsatzsammlung